NGUNJUNG CULTURAL COMMUNICATION AS A SOCIAL-POLITICAL PRACTICE: TRADITION, RELIGIOUS AUTHORITY, AND COMMUNITY COHESION IN INDRAMAYU - Dhini Ardianti; Indah Muina Hermawati1 (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2026)
Culture and communication are closely intertwined. Traditions handed down through generations must be safeguarded to ensure they are not lost to the passage of time. This study examines the communication situation, events, and actions within the Ngunjung culture. The research was conducted in Bongas District, Indramayu Regency, West Java, with a focus on the traditional Ngunjung ceremony. The study employed an ethnographic approach to communication, using qualitative methodology. Data collection methods included observation, in-depth interviews, and documentation. The analysis was qualitative and inductive, emphasising the meaning behind generalisations. Triangulation techniques were utilised to ensure the credibility and reliability of the findings. The findings revealed that the communication situation in Ngunjung culture is both sacred and celebratory. It is sacred because the traditional ceremonies are deeply rooted in Islamic beliefs, incorporating religious activities. Simultaneously, it is celebratory as the Bongas community also arranges traditional entertainment, such as skits, alongside pilgrimages. The communication events in Ngunjung culture are based on the historical narratives of Karmi's great-grandmother and Warji's great-grandfather, who were descendants of Sunan Gunung Jati. These figures were instrumental in imparting religious knowledge and were regarded as the oldest and most respected individuals in the Bongas region. Communication within Ngunjung culture encompasses both verbal and non-verbal forms. Verbal communication is evident in activities such as the tahlil akbar and tahlil during the Ngunjung ceremonies. Non-verbal communication is observed in the presence of tumpeng during the traditional ceremony.